2003
DOI: 10.4269/ajtmh.2003.69.151
|View full text |Cite
|
Sign up to set email alerts
|

Short Report: A Major Genotype of Japanese Encephalitis Virus Currently Circulating in Japan

Abstract: A 240-nucleotide sequence of the capsid/premembrane gene region of 23 Japanese encephalitis virus (JEV) strains isolated in Tokyo and Oita, Japan was determined and phylogenetic analyses were performed. All the strains clustered into two distinct genotypes (III and I). All strains isolated before 1991 belonged to genotype III, while those isolated after 1994 belonged to genotype I. In addition, the strains of the genotype I isolated in Japan showed a close genetic relationship with those from Korea and Malaysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 15 publications
4
63
0
2
Order By: Relevance
“…Before that time, genotype III was the most frequently isolated genotype in Japan. 14 Using the E gene sequences, we subdivided the isolates in this study into three clusters: A, B, and C ( Figure 4A ). There were 19-35 nucleotide differences among clusters A, B, and C ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before that time, genotype III was the most frequently isolated genotype in Japan. 14 Using the E gene sequences, we subdivided the isolates in this study into three clusters: A, B, and C ( Figure 4A ). There were 19-35 nucleotide differences among clusters A, B, and C ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…12,13 It has also been considered necessary to clarify how JEV strains were maintained in local areas after the most frequently isolated genotype changed from III to I in the 1990s 14 in Japan. A previous study of genetic change and variation in JEV genotype III in Taiwan 15 suggested that JEV isolates fall into three clusters by area and are genetically stable in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, all licensed inactivated and live-attenuated JE vaccines are derived from GIII JEV. However, the major genotype of JEV isolated in Japan changed from GIII to GI in the early 1990s (Ma et al, 2003;Yoshida et al, 2005). In recent years, a similar genotype shift has been observed in South Korea, northern Vietnam, China, Taiwan and Thailand Nam et al, 1996;Nga et al, 2004;Nitatpattana et al, 2008;Pan et al, 2011;Wang et al, 2007;Yang et al, 2004;Yun et al, 2010;Zhang et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…mosquitoes, from genotype III to genotype I, was witnessed in East Asia during the 1990s (11,12). These results and phylogenetic analysis of old JEV strains in Japan and Southeast Asia (11) strongly suggested that JEV could be transferred frequently from Southeast Asia to East Asia.…”
Section: Discussionmentioning
confidence: 61%